2019
DOI: 10.22271/ortho.2019.v5.i2j.73
|View full text |Cite
|
Sign up to set email alerts
|

Plating systems for 3D stability of subcondylar fracture: A research article with review of literature

Abstract: Mandibular condylar fractures are the most commonly seen fractures. Three dimensional Stable fixation is necessary for providing better stability. Comparison of different finite element studies and some base level pilot study correlating the imaging technique and implant material will enlighten the advantage of different plates as per different situations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 9 publications
0
1
0
Order By: Relevance
“…They concluded that the three-dimensional rhombus plates had clinical and radiographic outcomes comparable to the two miniplates, offering less operative time, with strong recommendation for high subcondylar fractures which is in agreement to the results of our study. (44) in 2019 compared five plating systems including two 4 hole double mini plate, Delta plate, inverted Y mini plate, Trapezoidal plate and Lambda plate and measured the anteroposterior width of the condylar neck on CT scans of 10 hemimandibles of healthy individuals and concluded that a single Trapezoidal plate fulfilled the criteria of functionally stable osteosynthesis on the condylar neck and provided greater functional and biomechanical stability due to its shape and configuration. They reported that the large surface area between the two plate arms and the minimal periosteal stripping required and the maximum preservation of proximal blood supply resulted in better healing.…”
Section: Ashor Et Almentioning
confidence: 99%
“…They concluded that the three-dimensional rhombus plates had clinical and radiographic outcomes comparable to the two miniplates, offering less operative time, with strong recommendation for high subcondylar fractures which is in agreement to the results of our study. (44) in 2019 compared five plating systems including two 4 hole double mini plate, Delta plate, inverted Y mini plate, Trapezoidal plate and Lambda plate and measured the anteroposterior width of the condylar neck on CT scans of 10 hemimandibles of healthy individuals and concluded that a single Trapezoidal plate fulfilled the criteria of functionally stable osteosynthesis on the condylar neck and provided greater functional and biomechanical stability due to its shape and configuration. They reported that the large surface area between the two plate arms and the minimal periosteal stripping required and the maximum preservation of proximal blood supply resulted in better healing.…”
Section: Ashor Et Almentioning
confidence: 99%
“…Geometric plate-a single L, Y plate, triangular plate, trapezoidal plate, delta plate or 3 D plates are used. Among all plates geometric plates provide the better stability and outcome, because it fulfills the criteria of functionally stable osteosynthesis in the fracture segments [20].…”
Section: Different Fixation Optionsmentioning
confidence: 99%